"Thank You for Your Sacrifice, I Will Try to Make Sure Your Donation Wasn't in Vain": Undergraduate Science Students' Perceptions on the Use of Cadaveric Material in Learning Anatomy - Natasha AMS Flack; Katie Frost; Shanmugapriya Aravazhi; Athena Macmillan; Phil Blyth; Stephanie J. Woodley; Helen D. Nicholson; Bradley J. Hurren; Rebecca J. Bird (MDPI AG, 2022)
Human-cadaveric material is a valuable resource for teaching anatomy, and a lot of research engaging medical students shows they benefit, in a variety of ways, from engaging with this material. However, more and more students who study anatomy are non-medical. Thus, they may have different educational foci than that of medical students, and, therefore, different perspectives on the value of human-cadaveric material as a learning resource. The aim of this study was to explore the perceptions of science students studying anatomy, in the use of learning using cadaveric material. Two cohorts of undergraduate science students studying anatomy (second-year, third-year) completed two surveys; one at the start and another following the completion of their semester-long courses that utilised prosections (second-year) and dissection (third-year) as a primary way of learning anatomy. Likert-scale and open-ended responses were analysed using a general inductive approach, and common emergent themes were identified. In total, 134 second-year and 77 third-year students completed the first survey, and 80 second-year and 36 third-year students completed the second survey. For the majority of students, their interactions with human material were positive and most of them cope well. Students acknowledged the opportunity and expressed gratitude for an invaluable learning resource. If at first the situation is confronting, with more experience, exposure, and staff support, most students find their initial concerns dissipate. This study identifies key areas of the learning journey that work well and others that can be improved, to better prepare students for learning with human material.